Sensitive Determination of C-Alkylated Flavonoids by HPLC-ESI-MS/MS Using Multiple Reaction Monitoring Approach: Pseudarthria hookeri as a Case Study. (1st November 2019) - Faraz, Ina; Ali, Arslan; Ul Haq, Faraz; Tchamgoue, Joseph; Kouam, Simeon F; Miana, Ghulam Abbas; Musharraf, Syed Ghulam
Abstract: One of the major problems with the formulation of herbal medicines is the quality control of plant material to ensure its efficacy and safety. Quality control of medicinal plants requires analysis of many bioactive compounds present in the plant. C-alkylated flavonoids are an important bioactive subclass of flavonoids. A simple, rapid, sensitive and selective method is presented here for the quantification of bioactive C-alkylated flavonoids. This is the first quantitative method for analysis of C-alkylated flavonoids based on the multiple reaction monitoring (MRM) approach so far. This study focuses on method development for quantification of bioactive C-alkylated flavonoids. Quantification of a total of five C-alkylated flavonoids was done employing the MRM approach on an HPLC-QqQ-MS instrument. LODs and LOQs for quantified flavonoids were in the range of 0.41–1.32 and 1.23–3.96 ng/mL, respectively. Linear calibration curves between 25 and 1500 ng/mL were obtained with the regression coefficients of ≥0.996. Accuracy (% bias) and precision (% RSD) of the analyses were found to be less than 5%. Developed HPLC-ESI-MS/MS can be employed as a quality control method of plant raw materials.